Lymphoepithelioma-like Carcinoma of the Breast: A Variant with Characteristic Histopathological and Immunohistochemical Features - Jansari, Trupti R.; Gupta, Tanvi; Trivedi, Priti P.; Shah, Manoj J. (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
The study aims to report a rare case of Lymphoepithelioma-Like Carcinoma of The Breast which may also aid in knowledge of literature to other colleagues. Lymphoepithelioma-like carcinoma (LELC) is an undifferentiated carcinoma, it occurs in the organs that exclude nasopharynx, but has the same morphology as that of nasopharangeal lymphoepithelioma. It has been described in several organs, however it is rarely seen in the breast. Due to the undifferentiated appearance of neoplastic cells and the presence of prominent lymphocytic infiltrate, LELC can wrongly be diagnosed as lymphoma and medullary carcinoma. In this case, we present the LELC of the breast in a 39 year-old woman with clinical, histological and immunohistochemical features with differential diagnosis.